ChemInform Abstract: A Mild and Efficient Procedure for the N‐Functionalization of S‐Perfluoroalkylated Aryl Sulfoximines. Issue 39 (5th September 2013) - Mace, Yohan; Constant‐Urban, Celine; Bouvet, Sebastien; Pegot, Bruce; Bournaud, Chloee; Toffano, Martial; Vo‐Thanh, Giang; Diter, Patrick; Magnier, Emmanuel
Abstract The title reaction is carried out with acid chlorides as reactants in the presence of base to give the corresponding functionalized amides.